2022
DOI: 10.48550/arxiv.2202.04680
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Joint Variational Multichannel Multiphase Segmentation Framework

Abstract: In this paper, we propose a variational image segmentation framework for multichannel multiphase image segmentation based on the Chan-Vese active contour model. The core of our method lies in finding a variable u encoding the segmentation, by minimizing a multichannel energy functional that combines the information of multiple images. We create a decomposition of the input, either by multichannel filtering, or simply by using plain natural RGB, or medical images, which already consist of several channels. Subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The workflow proposed in [6] consists of two steps, namely the input lifting, and the subsequent minimisation of the proposed energy functional. To achive the input lifting we apply K feature enhancing transforms Φ 1 , .…”
Section: Segmentation Methods Of [6]mentioning
confidence: 99%
See 3 more Smart Citations
“…The workflow proposed in [6] consists of two steps, namely the input lifting, and the subsequent minimisation of the proposed energy functional. To achive the input lifting we apply K feature enhancing transforms Φ 1 , .…”
Section: Segmentation Methods Of [6]mentioning
confidence: 99%
“…The regularisation parameter for the total variation (TV) is given by λ > 0. For the efficient minimisation of our energy functional in [6], we implement a non-convex version of the first-order primaldual algorithm proposed by Chambolle and Pock in [13,3]. In this recently submitted paper [6], we have shown that at least one global minimiser of (1) exists, as well as that the minimisation of the functional is stable with respect to perturbation of the image.…”
Section: Segmentation Methods Of [6]mentioning
confidence: 99%
See 2 more Smart Citations